Leadership Styles and Employee Engagement: A Field Study at a Qatari Public Corporation - Mahrameh, Thamer Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
The current study explored the relationship between leadership styles and employee engagement in the case of a Qatari public corporation. Survey research method was used in the research. In order to meet the research objectives, an online survey questionnaire was developed and distributed to a simple random sample of 294 employees. Descriptive and analytical statistical techniques available in SPSS were used to analyze the data of the 125 returned surveys. The results of the current study revealed that: (1) about 75% of the respondents are engaged in their work, (2) employees perceive their supervisors as transformational leaders rather than transactional leaders. Nonetheless, employees perceive their supervisors as neither pure transformational leaders nor pure transactional leaders, (3) there is strong and positive correlation between employee engagement and both transformational and transactional leadership styles. However, the correlation between transactional leadership and employee engagement was stronger than the correlation between transformational leadership and employee engagement. Based on that it is recommended to: (1) encourage supervisors to mix both transformational and transactional leadership styles by considering the situation and the nature of the task assigned to employees, (2) take action to develop leadership skills and behaviors, (3) show recognition for employee contributions and efforts, (4) strengthen the relationships between employees and their supervisors. In conclusion, it is important to develop strategies and practices to enhance employee engagement. One of the key factors in doing so is the development of leadership styles and behaviours.